Images of Realito Flamenco in Seville, 1929: Sevillanas, fandangos y tarantas entre guitarras y batas de cola - Heredia Martínez, Carmen (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This work analyzes stories 4-736 and 4-737 from the Fox Movietone News collection recorded in 1929. Artists such as Antonio y Rosario, Realito, Carbonerillo and Antonio Peana appear in it. The study methodology will use specialized and different bibliographies of photographs to carry out this work of documentary analysis. In the conclusions it was possible to verify the importance of Realito in the projection of the image of Spain. It has also been possible to appreciate that Carbonerillo’s songs that have been recorded in the films are not the most representative of the artist.